THE ANALYSIS OF INVENTORY VALUE ON MARKET VALUE BY PROFIT LOSS COMPONENT AS INTERVENING VARIABLE - Nova Begawati; Rida Rahim (JURNAL MANAJEMEN DAN BISNIS, 2020)
The aim of this research is to provide an empirical effect of inventory value on the market value of income, the cost of products sold and profit as intervening variables. Both firms belonging to manufacturing companies (food and beverage sub-sectors) in the period 2014-2018 on the stock exchange are the focus of this study. Indonesian Securities comprises 14 firms. The tool used is path was analysis using SPSS. The findings show that profits and expense of products sold do not have an indirect impact on the relationship between inventory value and market value as an intervening variable, while profit has an indirect effect on the relationship between inventory value and market value as an intervening variable.